(untitled) (Damu Journal of Sport Sciences, 2025)
Athletic performance in futsal is the result of a complex interaction between physical, technical, and psychological factors. Perceived self-efficacy is one of the most prominent psychological variables influencing performance quality under pressure and decision-making in competitive situations. This study aims to analyze the impact of perceived self-efficacy on player selection and predicting their athletic performance. A sample of (153) players from the Iraqi Futsal League was selected and subjected to self-efficacy measurements using a standardized scale, in addition to a technical and tactical performance evaluation form. The results showed statistically significant differences in performance levels depending on the degree of self-efficacy, with players with high self-efficacy outperforming. Regression analysis also demonstrated that self-efficacy contributes significantly to explaining the variance in athletic performance. The study recommends incorporating this psychological indicator into selection criteria and developing targeted training programs to enhance self-efficacy among players, supporting performance stability in competitive contexts.